TRIZ: an alternate way to solve problem for student - Tee, Tze Kiong; Saien, Shanty; Yee, Mei Heong; Mohamad, Mimi Mohaffyza (Human Resource Management Academic Research Society, 2017)
Inventive problem solving is an alternative way of solving problem for student. 60 years ago, in 1956, Altshuller published a new, constructive and methodical approach ideas on problem solving to offer to the world. Even though TRIZ originally meant for fields of industry domains, it has solved problems in other field using some common principles. Thus, this methodology has spread to over 35 countries across the world. It is now being taught in several universities and it has been applied by a number of global organizations who have found it particularly useful to solve their problem. In 2017, KSSM curriculum has been revised to cope up this 21st century demand. This paper is a potentially useful for TRIZ beginner, as an alternative to solve problem comparable to common problem solving method. This paper also discussed the limitation of other common problem method which leads the advantages of using TRIZ.